Maternal-fetal attachment and anxiety in pregnant women who conceived through assisted reproductive technology: A longitudinal study - Fahimeh Ranjbar; J. Catja Warmelink2comma 3comma; Robab Mousavi; Maryam Gharacheh (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Background: Pregnancy through assisted reproductive technology (ART) is a stressful experience that may affect prenatal attachment. However, maternal-fetal attachment (MFA) and anxiety in pregnancy after ART are understudied in Iran. Objective: To compare changes in MFA and pregnancy-related anxiety (PRA) in the first and third trimester of pregnancy in women who conceived through ART compared to those who conceived naturally. Materials and Methods: This longitudinal study was conducted in 2019 with 187 pregnant women (ART conception = 43, natural conception = 144). Participants were recruited using the consecutive sampling method from a prenatal clinic in Tehran. The Cranley MFA Scale and the Van Den Bergh PRA Questionnaire were used to collect the data. Results: The MFA score in the 12 th wk of gestation was lower in the women who conceived with ART compared to in the women who conceived naturally, but there was no statistically significant difference between the groups in wk 36. MFA in both groups was significantly higher at gestational wk 36 than wk 12 (p ≤ 0.001). The increase in MFA score was significantly higher in the women who conceived with ART than in those who conceived naturally (p ≤ 0.001). The anxiety score declined in the two groups and no statistically significant difference was observed in the changes of anxiety scores between the two groups (p = 0.84). Conclusion: Pregnant women who conceived through ART were as attached to their fetus in the third trimester of pregnancy as other women and did not experience more PRA.